2010
DOI: 10.1002/ptr.2939
|View full text |Cite
|
Sign up to set email alerts
|

Screening of binding activity of Streptococcus pneumoniae, Streptococcus agalactiae and Streptococcus suis to berries and juices

Abstract: Antiadhesion therapy is a promising approach to the fight against pathogens. Antibiotic resistance and the lack of effective vaccines have increased the search for new methods to prevent infectious diseases. Previous studies have shown the antiadhesion activity of juice from cultivated cranberries (Vaccinium macrocarpon Ait.) against bacteria, especially E. coli. In this study, the binding of two streptococcal strains, Streptococcus pneumoniae and Streptococcus agalactiae, to molecular size fractions (FI, FII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Therefore, several studies have focused on alternative strategies to cure pneumococcal infections 2224 . It has been known for a long time that plants are a source of antimicrobial compounds 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several studies have focused on alternative strategies to cure pneumococcal infections 2224 . It has been known for a long time that plants are a source of antimicrobial compounds 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it was shown that N. meningitidis pili , Streptococcus pneumoniae bacterial cells and Streptococcus agalactiae bacteria bind to berry molecular size fractions especially from Vaccinium species and they inhibit hemagglutination caused by Streptococcus suis (Toivanen et al ., 2009, 2010). The results (Toivanen et al ., 2009) showed that berry juice molecular size fractions of 10–100 kDa inhibited the binding of isolated N. meningitidis pili to membrane‐bound epithelial cells in a dot assay.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that juice fractions of different molecular size prepared from bilberry ( Vaccinium myrtillus ), blackcurrant ( Ribes nigrum ), cranberry ( Vaccinium oxycoccus ), crowberry ( Empetrum nigrum and hermaphroditum ) and lingonberry ( Vaccinium vitis‐idaea ) exhibit antiadhesion activity against a Gram‐negative human pathogen Neisseria meningitidis (Toivanen et al , 2009). Also binding or inhibitory activities of molecular size fractions prepared from Vaccinium berries and crowberry were shown against different pathogenic streptococcal strains of human or animal origin (Toivanen et al , 2010).…”
Section: Introductionmentioning
confidence: 99%